Responsibility inoculation: Constructing 'good parent' accounts when accessing child mental health services. Issue 1 (1st February 2021) - O'Reilly, Michelle; Kiyimba, Nikki
With the prevalence of child mental health conditions rising, the role of the initial mental health assessment is crucial in determining need. Utilising a critical discursive analytic framework, we explored the ways in which parents during these mental health assessments constructed the child's difficulties as medicalised and doctorable as opposed to systemic and familial. Through this discursive positioning, we examined the ways in which parents mitigated blame and accounted for the child's behaviours and emotions. Parents engaged in three accounting practices to construct the child's problems as dispositional and to mitigate against an alternative familial system interpretation. First, they drew upon normative cultural repertoires of parenting. Second, they mediated ways whereby normative practices were deviated from in the best interest of the child. Third, they rhetorically positioned overcoming systemic difficulties by illustrating cooperative parenting in separated families. Our findings have implications for how parents build a case for the need for medical intervention in assessment settings.